2004
DOI: 10.1111/j.1365-3156.2004.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two annual, single‐dose mass drug administrations of diethylcarbamazine alone or in combination with albendazole on soil‐transmitted helminthiasis in filariasis elimination programme

Abstract: SummaryA longitudinal community-trial on the control of soil-transmitted helminths (STHs), as part of a lymphatic filariasis elimination campaign, was taken up in two revenue blocks of southern India in the years 2001 and 2002 to assess the impact of two annual single-dose mass drug administration (MDA) of diethylcarbamazine (DEC) + albendazole (ALB) with that of DEC alone. The prevalences and intensities of STHs were studied among cross-sectional samples of school children aged 9-10 years by using the Kato-Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
4
11
1
Order By: Relevance
“…For areas endemic for W. bancrofti there are an increasing number of studies which show the positive effect of filariasis control using MDA with DEC combined with alb on the reduction of intestinal helminths [8-11,38]. The results of the present study can extend this observation to areas endemic for Brugia infections.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…For areas endemic for W. bancrofti there are an increasing number of studies which show the positive effect of filariasis control using MDA with DEC combined with alb on the reduction of intestinal helminths [8-11,38]. The results of the present study can extend this observation to areas endemic for Brugia infections.…”
Section: Discussionsupporting
confidence: 70%
“…This approach has been shown to reduce microfilaraemia of W. bancrofti and B. malayi efficiently [5-7]. Studies in areas endemic for W. bancrofti also indicate that the treatment with DEC combined with alb has the additional long-term beneficial effect of reducing prevalence and intensity of infection with intestinal helminths such as Ascaris lumbricoides , hookworms and Trichuris trichiura [8-11]. …”
Section: Introductionmentioning
confidence: 99%
“…A bounce back in STH infection levels was seen following treatment, but the difference in prevalence between albendazole and DEC- treated SAC compared to DEC-treated SAC remained significant (34.56% prevalence of STH in the intervention arm and 59.60% in control arm 11 months post-MDA) ( P <0.005)56. A subsequent study demonstrated that biannual MDA had greater benefit in keeping the prevalence of STH low following treatment (14.15% in intervention arm and 50.25% in control arm, 11 months post-two rounds of MDA, P< 0.001)57. After seven annual rounds of LF MDA from March 2001 to February 2010, STH prevalence was 12.48 per cent in the intervention arm, with hookworm showing the largest reduction with a final prevalence of 1.17 per cent, Ascaris 10.92 per cent and Trichuris 1.17 per cent ( P <0.05)58.…”
Section: Mass Drug Administration (Mda) Interventionsmentioning
confidence: 90%
“…Since the introduction of government-run MDA for lymphatic filariasis (LF) in endemic areas in 1998 in Tamil Nadu, several observational studies have documented the impact of mass interventions for STH in the community55565758. In Villupuram district, Tamil Nadu, community-wide MDA with albendazole and diethylcarbamazine (DEC) resulted in a decrease of STH (measured in a subgroup of children aged 9-10 yr) from 60.40 to 15.60 per cent [percentage reduction of Ascaris - 74.30% in intervention arm (albendazole with DEC) and 30.80% in control (DEC alone), hookworm reduction of 89.50% in intervention arm and 25.99% in the control arm, Trichuris reduction of 81.58% in intervention arm and 77.25% in the control arm]55.…”
Section: Mass Drug Administration (Mda) Interventionsmentioning
confidence: 99%
“…In Haiti, 2 annual single-dose MDAs with DEC (6 mg/kg) and albendazole (400 mg) reduced Ascaris , Trichuris and hookworm prevalences from 20.9% to 14.1%, 34.0% to 14.6%, and 11.2% to 2.0%, respectively, 9 months after the second MDA [68]. In India, the same treatment reduced the prevalence of Ascaris by 83%, Trichuris by 63% and hookworm by 69%, 11 months after the second MDA [69]. These “beyond-filariasis” benefits will not only give the anti-filariasis campaign a broader public health significance but also help to improve compliance among people and sustain the elimination program.…”
Section: Re-evaluation Of Low-dose Dec Treatment Introduction Of Newmentioning
confidence: 99%